A quality systems study of M.K. Screens, Inc. - Gupit, Romana; Reyes, Roberto G.; Sison, Wilbert M. (Diliman, Quezon City College of Engineering, 1996)
M.K. Screens Incorporated is the only local company that manufactures deep-well screens and gabions. This project study done on the company is limited only to the production of deep-well screens as the production of gabions do not have any problems with regard to quality. The findings of the group are: 1. Presence of high number of reworks 2. High Quality Costs 3. Lack of a pre-defined quality system/department that would handle quality related problems. The recommendation of the group are: 1. Establishment of a Total Quality Assurance Department 2. Introduction of Total Quality Management.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: M.K. Screens Incorporated; Manufacturing industry; Quality control